STUDY ON ANTIMICROBIAL RESISTANCE PATTERN IN A TERTIARY CARE HOSPITAL – AN OBSERVATIONAL RETROSPECTIVE STUDY - M, RANGAPRIYA; LORANCE, ALINA; VARGHESE, ANISHA MERIN; HANIF, ARSHI; S, ARUNA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The aim of the study was to monitor the magnitude and trends in antimicrobial resistance through surveillance programs and bacteriological diagnostic methods. Methods: The study research has performed a retrospective observational study for period of 6 months (Dec 2019–June 2020) to determine the antimicrobial susceptibility pattern on cultures of various specimens at Vivekanandha Medical Care Hospital. The resultant data were computed in Microsoft Excel. Analyses were expressed as the total number, frequencies, and percentage. Results: A total of 110 culture and sensitivity reports were collected from microbiology departments. Among the culture report, 84% accounted for gram-negative and 16% for Gram-positive organisms. Out of eight specimens, 15 different bacteria were identified and the most common bacteria were Klebsiella pneumonia (25%), E. coli (14%), Staphylococcus aureus (13%), and Pseudomonas aeruginosa (12%). Conclusion: The interferences from the present study can help in bridging the gap in future educations, training, and adequate decision-making.